2017
DOI: 10.1002/fsn3.490
|View full text |Cite
|
Sign up to set email alerts
|

Mineral composition of Tamarindus indica LINN (tamarind) pulp and seeds from different agro‐ecological zones of Uganda

Abstract: Mineral composition of dry Tamarindus indica LINN pulp and seeds was evaluated on samples collected from three different agro‐ecological zones of Uganda (Lake Victoria Crescent, and Eastern and West Nile). The objective of the study was to evaluate the mineral composition of T. indica pulp and seed samples from across Uganda's different agro‐ecological zones and land use types. Separately grounded samples of T. indica pulp and seeds were analyzed for Zn, Fe, Mg, P, Na, K, and Ca. The univariate analysis of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 19 publications
6
28
0
Order By: Relevance
“…This agrees with Okello et al. () who documented different growing climatic and environmental factors, plant parts used, plant management conditions, and length of storage before analysis. Additionally, Rasanu, Magearu, Matei, and Soceanu () reported that the amount of vitamin C in fruit depends on the precise variety of the fruit, the soil and climate in which it grew, and the length of time since it was picked.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This agrees with Okello et al. () who documented different growing climatic and environmental factors, plant parts used, plant management conditions, and length of storage before analysis. Additionally, Rasanu, Magearu, Matei, and Soceanu () reported that the amount of vitamin C in fruit depends on the precise variety of the fruit, the soil and climate in which it grew, and the length of time since it was picked.…”
Section: Discussionsupporting
confidence: 91%
“…And rancidity can be accelerated by moisture, air, and presence of some metals, which agrees with a report by Okello et al. (; ) who documented high levels of moisture content and mineral composition in the Lake Victoria Crescent agro‐ecological zone, which recorded high acid value.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations